Dual Identification and Analysis of Differentially Expressed Transcripts of Porcine PK-15 Cells and Toxoplasma gondii during in vitro Infection - Zhou, Chun-Xue; Elsheikha, Hany M.; Zhou, Dong-Hui; Liu, Qing; Zhu, Xing-Quan; Suo, Xun (Frontiers in Microbiology, 2016)
Toxoplasma gondii is responsible for causing toxoplasmosis, one of the most prevalent zoonotic parasitoses worldwide. The mechanisms that mediate T. gondii infection of pigs (the most common source of human infection) and renal tissues are still unknown. To identify the critical alterations that take place in the transcriptome of both porcine kidney (PK-15) cells and T. gondii following infection, infected cell samples were collected at 1, 3, 6, 9, 12, 18, and 24 h post infection and RNA-Seq data were acquired using Illumina Deep Sequencing. Differential Expression of Genes (DEGs) analysis was performed to study the concomitant gene-specific temporal patterns of induction of mRNA expression of PK-15 cells and T. gondii. High sequence coverage enabled us to thoroughly characterize T. gondii transcriptome and identify the activated molecular pathways in host cells. More than 6G clean bases/ sample, including > 40 million clean reads were obtained. These were aligned to the reference genome of T. gondii and wild boar (Sus scrofa). DEGs involved in metabolic activities of T. gondii showed time-dependent down-regulation. However, DEGs involved in immune or disease related pathways of PK-15 cells peaked at 6 h PI, and were highly enriched as evidenced by KEGG analysis. Protein-protein interaction analysis revealed that TGME49_120110 (PCNA), TGME49_049180 (DHFR-TS), TGME49_055320 and TGME49_002300 (ITPase) are the four hub genes with most interactions with T. gondii at the onset of infection. These results reveal altered profiles of gene expressed by PK-15 cells and T. gondii during infection and provide the groundwork for future virulence studies to uncover the mechanisms of T. gondii interaction with porcine renal tissue by functional analysis of these DEGs.